Bumiputra participation in construction industry / Osman Talib, Habsah Abdullah and Mohd Azmi A Halim - Talib, Osman; Abdullah, Habsah; A Halim, Mohd Azmi
This report is prepared as part of measuring of the ability of the graduating students in writing report by applying the proper techniques. Besides that it also give the students some experience in organising material as large scale. Besides that it is also to expose the student to the business environment in which report writing is one of the main tasks. As far as our group is concerned we have chosen the topic of "BUMIPUTRA PARTICIPATION IN CONSTRUCTION INDUSTRY" with a special focus on Syarikat Mohd Haji Sirat Binaan Sdn.Bhd.